A palavra pelas palavras: o haicai como acesso ao texto literário - Kleber Mazione Lima Ferreira (2016)
The following project aims to propose a poetry reading work to be developed inside a classroom, designed specifically to the poetry genre haiku. It is intended thereby stimulate the taste and the formation of new literature readers who are beginning to have contact with the literary art in their first moments of school life. In fact, it is essential to maintain an approximate dialogue of literature with other ways of aesthetic construction that also propose language strategies that widen forms of understanding, like the advertising texts. In this sense, this project understands that reading poetry is also to establish dialogues, and therefore mediation within the school operates as fundamental. Along these pathways to cope with a reading project inside the school is also contributing to the formation of literature readers teachers, who are engaged in multiple possibilities of poetry, approaching the reader to possible achievements of a word. Due to that, it seeks to establish poetry-reading workshops, aiming to investigate if haiku can be an important tool to change denotative / connotative expression plans for middle school students, whose literary reading needs to be stimulated as a school commitment.